Mesto besedotvorja v raziskavah poljskih govorov in narečij - Gala, Sławomir; Ostromęcka - Frączak, Bożena (Slavia Centralis, 2020)
The place of the study of word formation in the Polish dialectological research The paper highlights the role of word formation in defining Polish dialects and local dialects. Despite significant research accomplishments in word formation of non-standard Polish, the role of dialectal word formation is still insufficiently elucidated. The authors postulate further research in the field of dialects and local dialects.